Gut as an emerging organ for the treatment of diabetes: focus on mechanism of action of bariatric and endoscopic interventions - Haluzík, Martin; Kratochvílová, Helena; Haluzíková, Denisa; Mráz, Miloš (Journal of endocrinology, 2018)
Increasing worldwide prevalence of type 2 diabetes mellitus and its accompanying pathologies such as obesity, arterial hypertension and dyslipidemia represents one of the most important challenges of current medicine. Despite intensive efforts, high percentage of patients with type 2 diabetes does not achieve treatment goals and struggle with increasing body weight and poor glucose control. While novel classes of antidiabetic medications such as incretin-based therapies and gliflozins have some favorable characteristics compared to older antidiabetics, the only therapeutic option shown to substantially modify the progression of diabetes or to achieve its remission is bariatric surgery. Its efficacy in the treatment of diabetes is well established, but the exact underlying modes of action are still only partially described. They include restriction of food amount, enhanced passage of chymus into distal part of small intestine with subsequent modification of gastrointestinal hormones and bile acids secretion, neural mechanisms, changes in gut microbiota and many other possible mechanisms underscoring the importance of the gut in the regulation of glucose metabolism. In addition to bariatric surgery, less-invasive endoscopic methods based on the principles of bariatric surgery were introduced and showed promising results. This review highlights the role of the intestine in the regulation of glucose homeostasis focusing on the mechanisms of action of bariatric and especially endoscopic methods of the treatment of diabetes. A better understanding of these mechanisms may lead to less invasive endoscopic treatments of diabetes and obesity that may complement and widen current therapeutic options.